1989
DOI: 10.1161/01.cir.80.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional and Doppler-echocardiographic and cardiac catheterization correlates of survival in primary pulmonary hypertension.

Abstract: To determine correlates of survival in primary pulmonary hypertension, we compared 41 echocardiography-Doppler and nine catheterization parameters with outcome in 26 patients. Mean follow-up was 19.7 months in survivors; mean survival was 4.8 months in 16 nonsurvivors. Cox life-table univariate analysis correlated two echocardiographic, three Doppler, and three catheterization variables with poor survival (pc0.05), and xj analysis ensured the best critical values: severity of pericardial effusion, heart rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
1
5

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(125 citation statements)
references
References 38 publications
7
112
1
5
Order By: Relevance
“…These results were supported by comparable results for cardiovascular mortality in addition to correlations between RVEF and previously reported robust predictors of outcome in PAH, including cardiac index, right atrial pressure, TAPSE, NT-proBNP and SvO 2 [4,[20][21][22]. Collectively, these observations suggest measurement of RVEF may be a useful tool to evaluate the long-term prognosis of patients with PAH.…”
Section: Discussionsupporting
confidence: 84%
“…These results were supported by comparable results for cardiovascular mortality in addition to correlations between RVEF and previously reported robust predictors of outcome in PAH, including cardiac index, right atrial pressure, TAPSE, NT-proBNP and SvO 2 [4,[20][21][22]. Collectively, these observations suggest measurement of RVEF may be a useful tool to evaluate the long-term prognosis of patients with PAH.…”
Section: Discussionsupporting
confidence: 84%
“…PAB'nın yanı sıra, kalp odacık boyutları, duvar hareketleri ve ventrikül fonksiyonları, kapak morfolojileri, perikart sıvısı, konjenital kalp hastalıkları, kalp içi ve pulmoner şantlar hakkında bilgi verir. Bununla birlikte bazı ekokardiyografik bulgular (sağ atriyal genişleme ile sağ atriyum alan indeksi, perikardiyal efüzyon, interventriküler septum distorsiyonu -sol ventrikül eksantrisite indeksi, düşük kardiyak debi, pulmoner akselerasyon zamanının kısa oluşu, triküspit anülüsün sistolde apikale yer değiştirmesi (TAPSE, tricuspid annular plane systolic excursion), miyokardiyal performans indeksi gibi) fonksiyonel kapasite ve invazif hemodinamik bulgular gibi prognostik değere sahiptir (1)(2)(3). Bu nedenle PAH'tan şüphelenilen her hastaya ekokardiyografi yapılmalıdır.…”
Section: ) Ekokardiyografiunclassified
“…The earliest studies of PAH showed that increased right atrial (RA) pressure, decreased CI, and increased mean pulmonary artery (PA) pressure were predictors of death or lung transplantation [28][29][30][31][32]. While these findings were published in an era before effective therapy was available, they have generally (but not universally) been validated in more recent studies of patients at diagnosis or initiation of therapy [19,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Potential Surrogate and Intermediate End Points In Pah Hemodmentioning
confidence: 99%
“…While pericardial effusion presence and size are also associated with death or transplantation, this parameter is unlikely to be sufficiently discriminating for research purposes [32,38,44,45,47,77]. It is notable that the estimate of right ventricular systolic pressure from echocardiography has not been found to be predictive of outcome [32,44,45,74].…”
Section: Echocardiographymentioning
confidence: 99%